2018
DOI: 10.1038/s41598-018-28668-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and glutamine handling in the Sertoli cells of transgenic rats overexpressing regucalcin: plasticity towards lactate production

Abstract: Sertoli cells (SCs) possess the unparalleled ability to provide the germ line with growth factors and nutrients. Although SCs can oxidize amino acids, e.g., glutamine, they mostly metabolize glucose, producing high amounts of lactate, the germ cells preferential substrate. Regucalcin (RGN) is a calcium-binding protein that has been indicated as a regulator of cell metabolism. In this study, we investigated glucose and glutamine handling in the SCs of transgenic rats overexpressing RGN (Tg-RGN) comparatively wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…All these processes are embedded within the specific testicular microenvironment, including the Sertoli and the Leydig cells. The first guard the blood–testis barrier, control the number of germ cells via apoptosis, and are a major energy source for spermatogenesis (secrete lactate and produce ATP through lipid β-oxidation) [ 82 , 83 ]. The latter produce steroid hormones and cAMP, which accelerates cholesterol transport to the IMM and stimulates the production of ATP in the mitochondria [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…All these processes are embedded within the specific testicular microenvironment, including the Sertoli and the Leydig cells. The first guard the blood–testis barrier, control the number of germ cells via apoptosis, and are a major energy source for spermatogenesis (secrete lactate and produce ATP through lipid β-oxidation) [ 82 , 83 ]. The latter produce steroid hormones and cAMP, which accelerates cholesterol transport to the IMM and stimulates the production of ATP in the mitochondria [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact role of Glu in human testis is still under investigation. Amino acids, including Glu besides serving as nutrients in energy metabolism, they represent a significant signalling molecule in the regulation of complex physiological processes during spermatogenesis (Hu et al, 2004; Mateus et al, 2018; Plaitakis, Kalef‐Ezra, Kotzamani, Zaganas, & Spanaki, 2017; Storto et al, 2001; Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An autopsy study of bilateral normal testes showed a lower daily sperm production per testis by ~13% in the left side, positively correlated with both total testicular weight and weight of testicular parenchyma, which were about 10% lower in the left testis when compared to the right side 63 . An increase in Lac and Glu could probably be attributed to impairment of spermatogenesis in normal left testis, resulting in an increase in the demands for these metabolites by the left side 21,41–49 . Besides defective spermatogenesis, a possible increase in levels of OS in normal left testis might also contribute to the increase in Glu levels, a metabolite with known antioxidant effects in human testes 45 …”
Section: Age and Bilateralism Dependencementioning
confidence: 98%
“…4). 21,[41][42][43][44][45][46][47][48][49] Both Lac and amino acids represent important nutrients in energy metabolism during spermatogenesis. An autopsy study of bilateral normal testes showed a lower daily sperm production per testis by ~13% in the left side, positively correlated with both total testicular weight and weight of testicular parenchyma, which were about 10% lower in the left testis when compared to the right side.…”
Section: Age and Bilateralism Dependencementioning
confidence: 99%
See 1 more Smart Citation